55.1k views
5 votes
The value of x in this system of equations is 1

3x + y = 9
y=-4x + 10
1. Substitute the value of y in the first equation
2. Combine like terms
3. Apply the subtraction property of equality
4. Apply the division property of equality
3x + (-4x + 10) = 9
--x + 10 = 9
-I= -1
X=1
What is the value of y?
Y =
Done

2 Answers

6 votes

Answer:

6

Explanation:

just did it on edge <3

User Alexei Sholik
by
5.9k points
4 votes

Answer:

(1, 6)

Explanation:

If x = 1 then the first equation is 3(1) + y = 9, and so y = 6. The second equation is y = -4(1) + 10, or y = 6.

Thus, the solution to this system of equations is (1, 6).

User Shavonne
by
4.9k points